Mystical geographies of Cornwall - Phillips, Carl (2006)
This thesis seeks to contribute to a cultural and historical geography of the mystical through a detailed case study of Cornwall since the mid-nineteenth century. In doing so, it also aims to contribute to a contemporary Cornish Studies literature that has begun to reclaim alternative and forgotten cultural and historical narratives of Cornwall. After a short introduction, chapter two positions this thesis in relation to debates around the region as a unit of geographical inquiry and the mystical as a cultural and historical category. It also positions this thesis in relation to the contemporary Cornish Studies literature; while chapter three engages with debates around the use of archives, interviews and oral histories as research methodologies. Chapter four argues that the late nineteenth and early twentieth century Celtic-Cornish Revival was connected to a new and somewhat exploratory version of the mystical that drew upon Anglo-Catholic history and theology in the new Diocese of Truro and in the Cornish landscape, but that was also characterised by a certain degree of slippage beyond the discursive boundaries of Celtic Christianity. The mid-twentieth century, chapter five argues, was characterised by a series of strategies to normalise this earlier version of the mystical by engaging with, and actively incorporating, other and potentially contradictory versions of the mystical, and by grounding this more inclusive version of the mystical in a new, decentralised and more populist institutional context. In turn, chapter six argues that the later twentieth century was characterised by the emergence of another new and more exploratory cultural formation of the mystical through a particular culture of landscape that was underpinned by the supposed rediscovery of the principles of megalithic science and an associated revival of Paganism among other new social and religious movements. Chapter seven, in conclusion, reflects upon the often understated connections between the mystical and a sense of socio-spatial order, the problematic nature of knowledge, and the consequences of bringing together the mystical, the geographical and the Cornish in the context of this thesis and of existing and future work on the geographies of religion and spirituality.